2023
DOI: 10.1007/s12144-023-04908-3
|View full text |Cite
|
Sign up to set email alerts
|

Compassion fatigue and global compassion fatigue in practitioner psychologists: a qualitative study

Abstract: Practitioner psychologists are at risk of compassion fatigue (CF) due to the emotional demands of helping individuals who have experienced pain and suffering. Practitioner psychologists may also be impacted by wider socio-political events (such as the COVID-19 pandemic), which can lead to global compassion fatigue (GCF). While these concepts have been examined in various healthcare professionals, research exploring the impact of CF and GCF on practitioner psychologists has been very limited. This study therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It is not clear to what extent the global context at the time the study was conducted impacted the findings obtained. However, it is worthwhile considering the work ofStevens and Al-Abbadey (2023) who, in their study of professional psychologists, found that practitioners were at risk of experiencing compassion fatigue not only as a consequence of the emotional labour of working with clients' problems but also through exposure to the potentially distressing, unprecedented nature of global sociopolitical events-a phenomenon they term "global compassion fatigue." Further research with other trainee cohorts in a postpandemic training environment would, therefore, be beneficial in helping extend and refine the findings of this study.4.3 | Recommendations for future researchWhile definite themes emerged from the data, there appeared to be marked differences in how trainees experienced and adapted to the transition between modalities.…”
mentioning
confidence: 99%
“…It is not clear to what extent the global context at the time the study was conducted impacted the findings obtained. However, it is worthwhile considering the work ofStevens and Al-Abbadey (2023) who, in their study of professional psychologists, found that practitioners were at risk of experiencing compassion fatigue not only as a consequence of the emotional labour of working with clients' problems but also through exposure to the potentially distressing, unprecedented nature of global sociopolitical events-a phenomenon they term "global compassion fatigue." Further research with other trainee cohorts in a postpandemic training environment would, therefore, be beneficial in helping extend and refine the findings of this study.4.3 | Recommendations for future researchWhile definite themes emerged from the data, there appeared to be marked differences in how trainees experienced and adapted to the transition between modalities.…”
mentioning
confidence: 99%